An asteroseismic view of the radius valley: stripped cores, not born rocky - Van Eylen, Vincent; Lundkvist, Mia S. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Various theoretical models treating the effect of stellar irradiation on planetary envelopes predict the presence of a radius valley, i.e. a bimodal
Gesehen am 29.01.2019